Optimizing the Production Cost Budget as an Instrument for Planning and Cost Control at PT. Perkebunan Nusantara IV Kebun Panai Jaya - Widya Dwi Syahprya; Nur Ahmadi Bi Rahmani; Nurwani (LP2M IAIN Palopo, 2026)
This study aims to determine how the production cost budget is used as an instrument for planning and controlling production costs at PT. Perkebunan Nusantara IV (Persero) Kebun Panai Jaya. This study is expected to provide input for company management regarding the role of the budget as a planning and control tool. The research method used is qualitative research with a descriptive approach to explore budget fluctuations and production cost realization, as well as changes in budget productivity and production cost realization. The research subjects consisted of the Head of the Accounting Department, one accounting staff, and the Treasurer of the Finance Department of PT. Perkebunan Nusantara IV (Persero) Kebun Panai Jaya. Data collection was conducted through interviews with the finance department. The data analysis technique used is a method that collects, organizes, interprets, and analyzes data to solve problems encountered. The results of this study indicate differences between budgeted and realized production costs, as well as a decrease in productivity in certain years. The use of the budget must also be accompanied by a more in-depth variance analysis to identify the causes of deviations. Therefore, necessary steps can be taken to minimize adverse variances between the budget and actual results. Thus, the function of the budget as a planning and control tool can be more effective and efficient.